Evidence in the Corruption Case of Road Reconstruction - Sya’bania, Dewi Nabila; Auliany, Nafisa; Aziz, Hafizh Abdul; Chardena, Raincalosta Neodhy; Sangkut, Andi (Corruptio, 2023)
The state civil apparatus has an important role for the state, which is given the mandate and responsibility by the state and people in managing government affairs which become their respective functions and duties. The government apparatus in carrying out their duties must be good and full of integrity, because they are given trust by the government and society in carrying out their duties. People put their hopes on them to realize good governance in the future. However, the reality in the field is inversely proportional to what should be. In practice, the problem that often arises in the misuse of the duties of government officials is the practice of corruption. One of the cases of corruption that occurred in the field of procurement of goods or services was a case that occurred in North Lampung with the defendant named Yasril as the Commitment Making Officer at the PUPR Office of North Lampung Regency and the defendant Abdul Azim as his project partner. Yasril is considered to have neglected his duties as a Commitment Making Officer in the Kalibalangan Brach Four Road Widening Project, South Abung District, North Lampung Regency, in the 2019 fiscal year. The problem discussed in this study is how criminal liability for perpetrators of corruption crimes as in Decision Number: 3/Pid.Sus-TPK/2022/PN.Tjk and Decision Number: 4/Pid.Sus-TPK/2022/PN.Tjk? This research uses normative juridical research methods, namely research conducted based on primary legal materials by examining theories, concepts, legal principles and laws and regulations related to this research. It can be concluded that the prosecutor's method of proof was inaccurate and lacked caution in conducting the investigation, resulting in their imperfect indictment. So that the panel of judges did not believe in the results of the calculation of state financial losses submitted by the prosecutor's expert from the Public Accounting Firm Mahlizar, Jailani & Partners. This is because the calculation of state losses is based on procedures and procedures that do not contain certainty and are only based on assumptions. Thus, the panel of judges finally decided to acquit the two defendants from all charges.